2022
DOI: 10.3389/fimmu.2022.856186
|View full text |Cite
|
Sign up to set email alerts
|

Construction of a Novel LncRNA Signature Related to Genomic Instability to Predict the Prognosis and Immune Activity of Patients With Hepatocellular Carcinoma

Abstract: BackgroundGenomic instability (GI) plays a crucial role in the development of various cancers including hepatocellular carcinoma. Hence, it is meaningful for us to use long non-coding RNAs related to genomic instability to construct a prognostic signature for patients with HCC.MethodsCombining the lncRNA expression profiles and somatic mutation profiles in The Cancer Genome Atlas database, we identified GI-related lncRNAs (GILncRNAs) and obtained the prognosis-related GILncRNAs through univariate regression an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 97 publications
0
3
0
Order By: Relevance
“…RNA-seq data (level 3) and corresponding clinical information of 178 pancreatic cancer samples were obtained from TCGA database ( https://portal.gdc.cancer.gov/ ). The gene set [ 63 ] contained in the relevant pathway was analyzed using the GSVA package, with the parameter method = ‘ssgsea.’ The enrichment score of each sample on each pathway was calculated according to the ssGSEA algorithm [ 64 ] to obtain the sample, and the connection between the pathways. Finally, the correlation between FAT10 expression and EMT pathway score was analyzed by Spearman correlation.…”
Section: Methodsmentioning
confidence: 99%
“…RNA-seq data (level 3) and corresponding clinical information of 178 pancreatic cancer samples were obtained from TCGA database ( https://portal.gdc.cancer.gov/ ). The gene set [ 63 ] contained in the relevant pathway was analyzed using the GSVA package, with the parameter method = ‘ssgsea.’ The enrichment score of each sample on each pathway was calculated according to the ssGSEA algorithm [ 64 ] to obtain the sample, and the connection between the pathways. Finally, the correlation between FAT10 expression and EMT pathway score was analyzed by Spearman correlation.…”
Section: Methodsmentioning
confidence: 99%
“…Zhu et al constructed lncRNA signature with genomic instability to assess the prognosis and immune activity of patients with hepatocellular carcinoma (HCC). They found that the prognosis of high-risk patients was significantly worse, and the genomic instability score was related to chemotherapy drug sensitivity and immunotherapy effect of HCC patients [ 41 ]. Yang et al also constructed a signature composed of five lncrnas to assess the prognosis and immune characteristics of patients with pancreatic ductal adenocarcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the ssGSEA results indicated that the infiltration rate of most immune cells in the high-risk group was lower than in the low-risk group. Some of them were reported to be tumor antagonistic immune cells ( 32 , 33 ). In a previous study, the infiltration of activated CD8 T cells was proven to correlate to improved prognosis and survival of primary ovarian cancer ( 34 ).…”
Section: Discussionmentioning
confidence: 99%